Let
x = the first integer
x + 2 = The second integer
x + 4 = The third integer
- - - - - - - - -
x + x + 2 + x + 4 = 1509
3x + 6 = 1509
3x + 6 - 6 = 1509 - 6
3x = 1503
3x /3 = 1503 / 3
x = 501
The answer is: 501
- - - - - - - - - - -
The first integer x = 501
The second integer x + 2 = 501+ 2 = 503
The third x + 4 = 501 + 4 = 505
- - - - - - -s-
2007-01-12 06:31:30
·
answer #1
·
answered by SAMUEL D 7
·
0⤊
0⤋
Let the smallest/first number = x
So the other numbers are x+2 and x+4. Now, the sum of the numbers are as below:
x + x+2 + x+4 = 1509
3x + 6 = 1509;
3x = 1509 - 6 = 1503. So,
x = 1503/3 = 501. Therefore the first number is 501.
Other numbers are 503 and 505. That's all. I guess this is clear to you. All the best. = gsmani9 =
2007-01-12 06:36:18
·
answer #2
·
answered by mani 2
·
0⤊
0⤋
501 503 505 cos u just divide 1509 by 3, and then experiment with all the consecutive odd numbers that involve 503 (1509/3). So you get 499,501,503 OR 501,503,505, OR 503,505,507, and sure enough if u add them up, only 501+503+505 gives 1509 so theyre the answer
2007-01-12 06:23:44
·
answer #3
·
answered by ღ♥ღ latoya 4
·
0⤊
0⤋
i'd not use an equation. i might want to assert "The sum of any 3 abnormal integers will be abnormal, so there aren't any recommendations." If it changed into consecutive even integers, i might want to probable use the equation 2x + 2(x+a million) + 2(x+2) = seventy 2 however the equation x + (x + 2) + (x + 4) = seventy 2 might want to also be valid. (really i might want to probable basically say "the common is seventy 2/3 = 24, so the integers must be 22, 24 and 26.")
2016-12-02 04:19:11
·
answer #4
·
answered by ? 4
·
0⤊
0⤋
assume the three integers are :
n-2 , n , n+2
hence,
n-2 + n + n+2 = 1,509
3n = 1,509
n = 503
therefore, the three integers are :
503-2 , 503 , 503+2
501 , 503 , 505
2007-01-12 06:19:49
·
answer #5
·
answered by Psycho 3
·
0⤊
0⤋
501, 503, 505
2007-01-12 06:21:55
·
answer #6
·
answered by Brad K 3
·
0⤊
0⤋
501, 503, 505
2007-01-12 06:18:25
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
Sorry to all the people answering above, but the easiest solution is:
(x-2) + x + (x+2) = 1509.
3x = 1509
x = 503
x-2 = 501
x+2 = 505
2007-01-12 06:41:23
·
answer #8
·
answered by bequalming 5
·
0⤊
0⤋
x
x+2
x+4
x+x+2+x+4=1509
3x+6=1509
3x=1503
x=501
501, 503 and 505
2007-01-12 06:20:30
·
answer #9
·
answered by 7
·
0⤊
0⤋
501,503 and 505
2007-01-12 06:17:54
·
answer #10
·
answered by rodandalisonthompson 4
·
0⤊
0⤋